Glucose-Regulated Protein 78 Signaling Regulates Hypoxia-Induced Epithelial–Mesenchymal Transition in A549 Cells - Sun, Ling-Ling; Chen, Chang-Ming; Zhang, Jue; Wang, Jing; Yang, Cai-Zhi; Lin, Li-Zhu (Frontiers in Oncology, 2019)
Objective: Metastasis and therapeutic resistance are the major determinants of lung cancer progression and high mortality. Epithelial–mesenchymal transition (EMT) plays a key role in the metastasis and therapeutic resistance. Highly expressed glucose-regulated protein 78 (GRP78) is a poor prognostic factor in lung cancer and possibly correlated with EMT. This study aims to examine whether the up-regulation of GRP78 is involved in EMT in lung adenocarcinoma and explore the underlying downstream molecular pathways. Study design: EMT was assessed by analysis of cell morphology and expression of EMT protein markers in A549 cells under normoxia, hypoxia and silencing GRP78 conditions. The expression levels of Smad2/3, Src and MAPK (p38, ERK and JNK) proteins were examined by Western blot analysis under hypoxia and treatments with phosphorylation inhibitors. Results: Under hypoxic conditions, the EMT morphology significantly changed and the GRP78 expression was significantly up-regulated in A549 cells compared with those in normoxia control. The expression and phosphorylation levels of smad2/3, Src, p38, ERK and JNK were also upregulated. When GRP78 was silenced, EMT was inhibited, and the levels of phospho-smad2/3, phospho-Src, phospho-p38, phospho-ERK and phospho-JNK were suppressed. When the activation of Smad2/3, Src, p38, ERK and JNK was inhibited, EMT was also inhibited. The inhibition effect on EMT by these phosphorylation inhibitors was found to be weaker than that of GRP78 knockdown. Conclusions: Hypoxia-induced EMT in A549 cells is regulated by GRP78 signalling pathways. GRP78 promotes EMT by activating Smad2/3 and Src/MAPK pathways. Hence, GRP78 might be a potential target for treatment of lung adenocarcinoma.